Respuesta :

Answer:

Please be careful with your typing [f(x)=-sqrt(x)+6 ... right? g(x)=-4*sqrt(x)-3 ... or -4*sqrt(x)+3 ... one or the other, right?

If so, you are dilating by a factor of 4, -1 versus -4 as multiplier of sqrt(x); and, translating up 3 units (6 versus 3) or 9 units (6 versus -3).

Step-by-step explanation:

Answer:

-2x+2

Step-by-step explanation:

f(x) = -4x+3 and g(x) = 3 +2x-4

Note what you put for g(x) simplifies to 2x-1

(f+g) (x) =  -4x+3+  3 +2x-4

Combine like terms

            = -2x+2

ACCESS MORE